The Evaluation of Factors Affecting the Amount of DNA Obtained from Fired Cartridge Cases - Eda Nur Ay; Yakup Gülekçi; Fatma Ebru Yüksek; Harun Şener; Yeşim Tunç (Adli Tıp Bülteni, 2024)
Objective: It involves the evaluation of the effects of different biological materials deposited on cartridge cases on the amount of DNA recovered post-firing, considering the influence of time and different types of swabs Methods: MKE 9x19 mm brass cartridges were contaminated with blood and epithelial cells, fired, and swabbed at different intervals (1 day, 1 week, 2 weeks, 3 weeks, 4 weeks, 2 months, 3 months) to assess DNA quantity. The study compared microfiber and cotton swabs, utilizing the phenol-chloroform method for DNA extraction and the Quantifiler Trio kit with the 7500 real-time polymerase chain reactionsystem for quantification. Results: According to the AmpFlSTR™ Identifiler™kit, eight cartridge cases fell within the high-quality DNA profile range (0.05-0.125 ng/µL). One of these is an epithelium- contaminated cartridge, while the others are blood-contaminated cartridges. For cotton swabs, the highest degradation rate was obtained in the 4th week for blood contaminated cases, 2nd weeks for epithelial cell-contaminated cases. For microfiber swabs, the highest degradation rate was obtained in the 3rd month for blood contaminated cases, 1st day for epithelial cell-contaminated cases. In a study using cotton and microfiber swabs to collect samples from different biological materials on cartridge cases, no significant difference was found in DNA quantity between the swab types on day 1 and month 3. Conclusion: The microfiber swab, considered an alternative to the routinely used cotton swab, did not demonstrate superiority. DNA sufficient for successful profiling was obtained even from cartridges swabbed three months after firing. Additionally, blood-contaminated cartridges had significantly higher DNA levels than those contaminated with epithelial cells.